Neotropical region: a shapefile of Morrone’s (2014) biogeographical regionalisation - Löwenberg-Neto, Peter (Zootaxa, 2014)
In biogeography, spatial comparisons provide a quantitative assessment of the overlap between taxic distributions and areas. This information is used to describe taxonomic geographic distributions employed in further analyses. Spatial comparisons were traditionally made by visually comparing points of geographic occurrence against a map of areas, such as provinces or regions. A more precise way to conduct this task is using Geospatial Information Systems (GIS). To improve the quality of future analyses, we aimed at providing a vector file of the biogeographical regionalisation by converting the published map into a polygon shapefile.